Pandemic Pathways: Exploring Maternal Healthcare Utilization in Lucknow District - Anwar, Shadma; Anwar, Sanober; Hasan , Areeba; Khatoon , Ruby; Masood , Jamal; Zaidi, Zeashan H (National Journal of Community Medicine, 2025)
Background: For all women to have access to respectful and excellent maternity care, it is essential to address the inequities that have an impact on health outcomes. The COVID-19 pandemic showed significant challenges for countries continue providing essential maternal and neonatal health services. This study aims to assess maternal healthcare service utilization during the COVID-19 pandemic in Lucknow district. Methodology: A community based cross sectional study was conducted by using WHO 30 cluster sampling technique to the participants. Total sample size obtained was 30 clusters in rural and 30 clusters in urban area. Results: The results showed that 36.7% of urban and 41.0% of rural beneficiaries had poor MCH service utilization (<50%), with a further decline compared to pre-pandemic levels. In urban areas, 37.6% and 38.1% in rural areas used 50%-75% of services. Social class was significantly linked to MCH utilization (p<0.001), emphasizing the need to address disparities and improve access. Conclusions: The COVID-19 pandemic disrupted multiple aspects of maternal healthcare, exacerbated by health facility conversions, resource reallocations, and mobility restrictions. Addressing these systemic challenges is critical for ensuring resilient maternal healthcare services in future crises.